We have to turn a transatlantic liner—Leaders' perspectives on creating a meaningful life for older persons receiving municipal care - Annica Kihlgren; Inger James; Margaretha Norell Pejner (Nursing Open, 2023)
Abstract Aims To describe leaders’ perspectives on what is important to create a meaningful daily life for older persons receiving municipal elderly care. Design This study combined the Participatory Appreciative Action Reflection approach and qualitative methods. Methods Focus Group Discussions were performed with eighty leaders that was analysed with qualitative content analysis. Results One overall theme emerged “We have to turn a transatlantic liner”. The leaders proposed a need to change from an institutional care to a more person‐centered care approach on all levels of the healthcare system. This meant that everyone in the organization needed to think outside the box and find new ways to provide care to older persons. They needed to hire the right persons with the right values and knowledge. The leaders would need to provide for and support staff empowerment. There was also a need to see the older person and their relatives as co‐participants. No Patient or Public Contribution.